1989
DOI: 10.1039/p29890001647
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics, isotope effects, and mechanism of the reaction of 1-nitro-1(4-nitrophenyl)alkanes with DBU in acetonitrile

Abstract: The kinetics of the reaction of O,NC,H,C(L)(R)NO, (R = Me, Et, Pri, NNPE, NNPP, or MNNPP, respectively; L = H, D) with 1,8-diazabicyclo[5.4.O]undec-7-ene (DBU) in acetonitrile (MeCN) are reported. The nature of the product indicates that substantial dissociation into free ions occurs. The usefulness of Benesi-Hildebrand relationship for distinguishing between ion pairs and ions of the product is discussed in detail. The reaction shows l o w activation enthalpy value AHS = 15.4, 17.8, and 19.9 kJ mol-' and larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…cular proton transfer reaction gave a dissociated product in MeCN to a large extent, contrary to earlier reports (2)(3)(4)(5). Therefore the applicability of the Benesi-Hildebrand method (6) has been carefully discussed, to explain why it gave incorrect results in previous papers, published by different authors ( 1 ) . We also found large values of the primary deuterium kinetic isotope effect (KIE) despite the high polarity of the solvent, acetonitrile (MeCN), in which the reaction was carried out.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…cular proton transfer reaction gave a dissociated product in MeCN to a large extent, contrary to earlier reports (2)(3)(4)(5). Therefore the applicability of the Benesi-Hildebrand method (6) has been carefully discussed, to explain why it gave incorrect results in previous papers, published by different authors ( 1 ) . We also found large values of the primary deuterium kinetic isotope effect (KIE) despite the high polarity of the solvent, acetonitrile (MeCN), in which the reaction was carried out.…”
Section: Introductionmentioning
confidence: 63%
“…This suggested that the reactions in polar solvents follow an uncoupled mechanism (19) in which solvent reorganization precedes the proton transfer step, and is supported by the fact that the energy of activation is a complex function in which the part corresponding to the solvation effects in ionogenic reactions usually prevails (20). Taking into account that this idea is inconsistent with previously published results (7,(15)(16)(17)(18), the intention of the present paper is to approach the problem using two different solvents, tetrahydrofuran (THF) and chlorobenzene (CB), for the series of reactions of 1-(4-nitropheny1)-1 -nitroalkanes that have already been studied in MeCN solvent (1). We purposely chose THF and CB solvents because of the dramatic difference in KIE (12.7 and 50) previously found by Caldin et al (18) for similar reactions.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…These results show that the steric factor and ordering effects in forming the transition state play an important role, confirmed by negative and relatively large entropies of activation: ∆S ‡ = -149.7, -176.5, -178.7, -227.8 J mol -1 K -1 . The reactions between nitroalkanes with different steric hindrance and classic nitrogenous bases such as amidines or guanidines in acetonitrile and tetrahydrofuran have been disscussed previously [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%